Analysis of PLXNA1, NRP1, and NRP2 variants in a cohort of patients with isolated hypogonadotropic hypogonadism. Issue 11 (11th October 2021) - Men, Meichao; Chen, Dan‐Na; Li, Jia‐Da; Wang, Xinying; Zeng, Wang; Jiang, Fang; Zheng, Ruizhi; Dai, Wenting
Abstract: Background: Isolated hypogonadotropic hypogonadism (IHH) is a clinical syndrome described by failure of gonadal function secondary to defects on the synthesis, secretion, or action of the gonadotropin‐releasing hormone (GnRH). The secreted glycoprotein SEMA3A binds its receptors NRP1 or NRP2 and PLXNA to participate in axonal projection, dendritic branching, synaptic formation, and neuronal migration. Deficiency in SEMA3A, NRP1, NRP2, and PLXNA1 have been related to abnormal GnRH neuron development in mice and IHH in humans. Methods: The aim of this study was to examine the genotypic and phenotypic spectra of the NRP1, NRP2, and PLXNA1  genes in a large cohort of IHH probands from China. We screened NRP1, NRP2, and PLXNA1 variants in Chinese IHH patients by whole exome sequencing and pedigree analysis. Results: We identified 10 heterozygous missense variants in PLXNA1, five heterozygous missense variants in NRP1, and two heterozygous missense variants in NRP2 . NRP1 variants were found only in IHH patients with defective olfaction (i.e., Kallmann syndrome, KS). In addition, 85% (17/20) of patients harbored variants in other IHH‐associated genes. Conclusion: Our study greatly enriched the genotypic and phenotypic spectra of PLXNA1, NRP1, and NRP2 in IHH. It may be conducive to the genetic counseling, diagnosis, and treatment of IHH with mutations in the PLXNA1, NRP1, and NRP2  genes. Furthermore, our results indicated that NRP1 were strongly linked to hearing loss. Abstract : Our study greatly enriched the genotypic and phenotypic spectra of PLXNA1, NRP1, and NRP2 in IHH. It may conducive to the genetic counseling, diagnosis, and treatment of IHH with mutations in the PLXNA1, NRP1, and NRP2 genes. Furthermore, our results indicated that NRP1 were strongly linked to hearing loss (2/8 individuals).